2011
DOI: 10.29309/tpmj/2011.18.01.1859
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Fever

Abstract: One of the major health hazards that has erupted in Pakistan within the recent past years and has caused loss of life of many young people is Dengue Fever. Objective: Main objective was to find clinico-pathologic parameters which are essentially associated with complications and contribute to the adverse outcome. Material & Methods: This prospective study was conducted on 106 seropositive cases of dengue fever. Patients were taken from Abbasi Shaheed Hospital, Karachi from June 2008 to March 2009. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…It may persist in first week but once recovery starts, leucopenia will be replaced by increase in counts. As per study done by Arshad I, et al 24 , 49% patients had leucopenia less than 4000 /cu mm but Ledika MA, et al 22 found leucocyte counts >5000/cu mm in 78.3% patients. Other common haematological findings were raised haematocrit or fall of haematocrit after giving intravenous fluids by 20% found in 52% patients which was not statistically significant (p=0.091).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It may persist in first week but once recovery starts, leucopenia will be replaced by increase in counts. As per study done by Arshad I, et al 24 , 49% patients had leucopenia less than 4000 /cu mm but Ledika MA, et al 22 found leucocyte counts >5000/cu mm in 78.3% patients. Other common haematological findings were raised haematocrit or fall of haematocrit after giving intravenous fluids by 20% found in 52% patients which was not statistically significant (p=0.091).…”
Section: Discussionmentioning
confidence: 75%
“…It was found to be more common in patient with severe dengue infection. Arshad I, et al 24 , found that low platelets count below 50,000/cu mm was associated with poor outcome of the disease. Similarly, studies conducted by Prathyusha CV, et al 21 and Dhooria G, et al 25 also found poor correlation between thrombocytopenia and bleeding diathesis.…”
Section: Discussionmentioning
confidence: 97%
“…The people who get sick with dengue, their symptoms can be mild or severe [2,6]. People with mild symptoms can be confused with other diseases that cause fever, aches, pains, or cutaneous rash.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Transmission among human beings occurs by the mosquito Aedes and chiefly occurs during the rainy season [4]. DF is a severe infection that involves individuals of all age groups (infants, children, adolescents, and adults) [5] DF is also known as breakbone fever because of the associated myalgia and pain in joints [6]. The Ministry of Health in Sudan registers current further outbreaks of dengue disease and 'acute hysteria.…”
Section: Introductionmentioning
confidence: 99%
“…It may be difficult to diagnose dengue fever in the initial stage of the disease because the clinical presentations are almost similar to any other viral illness. [9] There are four serotype of dengue viruses DEN 1, DEN 2, DEN 3, and DEN 4. Infection with dengue virus can cause three clinical syndromes with undifferentiated febrile illness or viral syndrome, classical dengue fever (DF), dengue haemorrhagic fever (DHF) which may occur with shock or as dengue shock syndrome (DSS).Classical dengue fever (DF) is generally self-limited and is characterized by fever and a variety of non-specific signs and symptoms such as headache, malaise, weakness, rash and body aches.…”
Section: Introductionmentioning
confidence: 99%